2023
DOI: 10.3390/app13095618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Ventilation System by Using Jet Fans during a Fire in Road Tunnels

Abstract: People inside a road tunnel may be in grave danger if there is a fire. When a fire is developing, mechanical ventilation can be crucial in protecting occupants and facilitating the arrival of emergency crews. In this paper, a new calculation method that can analyze the evolution of the fire and of the airflow is illustrated. An assumed fire inside an 800 m long one-way road tunnel in Northern Italy was dealt with using the developed method. Subsequently, the acquired results were successfully compared to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Numerous scholars have discovered that thermal resistance arises from the heating of air by a fire source, causing changes in its density and other factors that impact its resistance [8,9]. In the study, a strong correlation was observed between the thermal resistance magnitude and the degree of temperature rise.…”
Section: Introductorymentioning
confidence: 90%
“…Numerous scholars have discovered that thermal resistance arises from the heating of air by a fire source, causing changes in its density and other factors that impact its resistance [8,9]. In the study, a strong correlation was observed between the thermal resistance magnitude and the degree of temperature rise.…”
Section: Introductorymentioning
confidence: 90%